If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -6x = 7 Solving -18 + -6x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6x = 7 + 18 Combine like terms: -18 + 18 = 0 0 + -6x = 7 + 18 -6x = 7 + 18 Combine like terms: 7 + 18 = 25 -6x = 25 Divide each side by '-6'. x = -4.166666667 Simplifying x = -4.166666667
| 0.5-1.4= | | M=20+3m | | 6-2x=5-3x | | z^4+2i=0 | | 10X-5=-80 | | 7+(x-3)-(x-3)=5-(3-x) | | 2(x+10)+2x=168 | | p(x)=x^2+2xfindp(1) | | 3xsquare-243=0 | | 4x-10=-20 | | 3(2c+d)-2d= | | 4*e^5x+1=9 | | (7-3x)(2x-6)=-42 | | x^3-21x-90=0 | | (y/4)-3=y/3 | | x^3-21x-90= | | (3x-2)(3x-2)=20 | | y=-0.0980392156863x+15.0196078431 | | x-21x-90=0 | | 3(2x-1)=3x+6 | | x(12-2x)(10-2x)=0 | | y/4-3=y/3 | | 3n+2=-40 | | -3-20=-x+10 | | x+y=365 | | 6x+4=9x-17 | | 10x-3y+3x-4y=0 | | 3x-2=-47 | | 21(w-937)=630 | | 0=8+4x | | 7x-11=x+1 | | -47+5x=30-2x |